Real-time monitoring of water level : a review of existing applications, and advancements in mini-telemetry system for agricultural planning. - Maneekul, Pongnathee; Suwannapong, Chanwit (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2017)
Recent advances in sensor technology have advantage in agricultural and water management. This paper presents an application of a small telemetry system to real-time water level management. The system has been developed by using a wireless sensor network, which automatically record the level of water to minicomputer(Raspberry Pi). The water level data collected at the end of a rainy season over six months period were converted to water volume. The water volume was then used as a model constraint for the agricultural acreage at Nam-Kam irrigation basin, Nam-Kam Sub-district, That-Phanom District, Nakhon Phanom Province, Thailand. The Differential Evolution algorithm (DE) was employed to modeling optimal water management. The results showed the suitable planting portion plan over the considered period for second rice: cassava: yam bean : tobacco were 83.76, 7.94, 8.02 and 0.27 percent, respectively.